Facing death: How does the subterranean termite Coptotermes gestroi (Isoptera: Rhinotermitidae) deal with corpses? - da Silva, Luiza Helena Bueno [UNESP]; Haifig, Ives; Costa-Leonardo, Ana Maria [UNESP] (Elsevier, 2019)
Social insects display a range of sophisticated behaviors to deal with cadavers, which together act to guarantee the health and social homeostasis of their colonies. In termites, cadaver management involves an entire repertoire of activities, such as antennation, grooming, retreat, alarm and agonistic behaviors. We performed different bioassays to evaluate whether postmortem-age, origin and caste of a cadaver influence the behavior of Coptotermes gestroi. Quantitative analyses of corpse management behaviors indicated that C. gestroi is able to discriminate the origin and caste of cadavers. Cadavers of worker nestmates were preferentially cannibalized while corpses of alien workers were buried. In addition, soldiers that had been dead for 24 hours were buried while freshly dead soldiers were either buried, consumed or ignored, indicating a plastic behavioral response that depends on postmortem age. Corpse consumption is an important component of corpse management repertoire because this process eliminates contaminant and enables nutrient recycling. The physical isolation of the termite corpse through burial after grooming also helps to prevent other colony members from contacting the cadaver, further mitigating against the potential spread of disease.
Keywords: Cadavers; Cannibalism; Hygienic Behavior; Undertaking Behavior